2018
DOI: 10.1121/1.5023594
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving foreign-accented speech with decreased spectral resolution in single- and multiple-talker conditions

Abstract: To determine the effect of reduced spectral resolution on the intelligibility of foreign-accented speech, vocoder-processed sentences from native and Mandarin-accented English talkers were presented to listeners in single- and multiple-talker conditions. Reduced spectral resolution had little effect on native speech but lowered performance for foreign-accented speech, with a further decrease in multiple-talker conditions. Following the initial exposure, foreign-accented speech with reduced spectral resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…CI users have also been found to have more difficulty recognizing highly variable speech produced by multiple talkers from different dialect regions (e.g., Sommers et al, 1997;Tamati et al, 2020) and foreignaccented talkers (Ji et al, 2014;Kapolowicz et al, 2020), compared to idealized lab speech, which typically involves carefully articulated speech produced by a single talker with no discernable accent. Similarly, studies using simulations of CI hearing have also reported less accurate recognition of highly variable speech (Faulkner et al, 2015) and foreignaccented speech (Kapolowicz et al, 2016(Kapolowicz et al, , 2018. Thus, although CIs improve hearing, different sources of indexical variability may pose substantial problems to speech recognition.…”
Section: Research Notementioning
confidence: 99%
“…CI users have also been found to have more difficulty recognizing highly variable speech produced by multiple talkers from different dialect regions (e.g., Sommers et al, 1997;Tamati et al, 2020) and foreignaccented talkers (Ji et al, 2014;Kapolowicz et al, 2020), compared to idealized lab speech, which typically involves carefully articulated speech produced by a single talker with no discernable accent. Similarly, studies using simulations of CI hearing have also reported less accurate recognition of highly variable speech (Faulkner et al, 2015) and foreignaccented speech (Kapolowicz et al, 2016(Kapolowicz et al, , 2018. Thus, although CIs improve hearing, different sources of indexical variability may pose substantial problems to speech recognition.…”
Section: Research Notementioning
confidence: 99%
“…Presentation of these five talkers was randomly interspersed for each block, and listeners heard each talker twice per block (additional details regarding blocks are described below). Data from both unshifted foreign-accented conditions were reported in our previous work (Kapolowicz et al, 2018), and again, presented here to allow for direct comparisons between shifted and unshifted speech. Since listeners were different for each condition, and all listeners shared the same relevant demographical information, statistical comparisons across conditions are allowed; (c) for the Foreign-Accented Single Talker Shifted condition, listeners heard unshifted speech as well as spectrally shifted speech from the same foreign-accented talker (randomly selected for each listener from one of the five talkers in the Foreign-Accented Multiple Talkers Unshifted condition) across 40 sentences to simulate five different talkers.…”
Section: Design and Proceduresmentioning
confidence: 77%
“…When these cues vary as they do across different talkers, rapid adaptation is impaired. Conversely, we did not expect spectral shifts to affect intelligibility of native-accented speech, since our previous work using the same paradigm found no difference in intelligibility scores across single-talker and multipletalker conditions (Kapolowicz et al, 2018). The native-accented spectrally shifted condition was included for comparative purposes and to demonstrate that listeners have no trouble perceiving spectrally-shifted native-accented speech using the signal processing implemented in the present work, which resulted in clean speech signals, with minimal artifacts/distortions that could affect intelligibility (as tested in Experiment 2).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations